[PP.32.14] CIRCADIAN BLOOD PRESSURE PROFILE AND TARGET ORGAN DAMAGE IN HYPERTENSIVE PATIENTS. SINGLE PILOT HYPERTENSION CENTER STUDY. (September 2016) - Tilea, I.; Mitre, A.; Carasca, C.; Varga, A.
Abstract : Objective: Long term proper management of hypertensive patients in family medicine practice in order to reduce cardiovascular events emphasize the global interest for active early diagnostic and accurate risk stratification in hypertension. Increased use of ambulatory blood pressure monitoring (ABPM) by trained family physicians will allow identification of different hypertension subtypes and their correlations with target organ damage. Design and method: 60 hypertensive patients from the evidence of a family medicine practice were evaluated according to a standardized protocol in a single pilot hypertension center. All patients underwent 24-hour ambulatory BP monitoring (ABPM); rest electrocardiogram (ECG) was performed. Echocardiographic left ventricular hypertrophy (LVH) was assessed and intima media thickness was evaluated. Renal organ damage was evaluated. Results: Circadian blood pressure profile was classified according to the ABPM; 28 (46.66%) dipper hypertensive patients, 24 (40%) patients with a non-dipping profile (non-dippers), 3 (5%) hypertensive patients with reverse-dipper BP profile and 5 (8.33%) hypertensive patients with extreme-dipper circadian BP profile. Left ventricular hypertrophy was present in 48.33% hypertensive patients; in contrast ECG evaluation showed LHV in 23.3% (14) patients. Obesity and smoking were not associated with LVH, (p < 0.05) in any identified hypertension profiles. Of all hypertensive patients, 31 (51.66%) were stratified in stage 2 CKD and 10 (6%) patients with severe renal damage (CKD stage 3 and 4). Non-dipper and reverse dipper hypertensive patients presented significant correlation between renal damage and LVH (p < 0.02). Conclusions: Real data from family medicine offices are missing. Specific centers involved in long-term monitoring hypertensive patients are needed.